KEBIJAKAN HUKUM PIDANA DALAM PENYELESAIAN TINDAK PIDANA RINGAN YANG DILAKUKAN OLEH LANSIA MELALUI PENDEKATAN RESTORATIVE JUSTICE - Ramadatul Fajri; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Nowadays, the perpetrators of criminal offense come from various circles,one of which is carried out by people who are elderly, according to existingregulations, the elderly are included in the vulnerable category which is entitledto more treatment and protection with respect to their specificity, but in practicein positive law In Indonesia, there are no rules governing the protection of theelderly who are in conflict with the law, before the law the elderly are stillequalized with perpetrators of criminal offense of productive age. In theimplementation of law enforcement against perpetrators of criminal offense of theelderly, it is still necessary to review the problem of law enforcement and effortsto resolve criminal offense, restorative justice in terms of acting as a media thatbridges the settlement of criminal offense by approaching or mediating betweenperpetrators and victims.The purpose of this study are: first, to determine legal policy towards theelderly, second, to determine the arrangements for efforts to resolve criminal actsby the elderly through a restorative justice approach. This type of research can beclassified as normative research or better known as "legal research". Thisnormative research uses a type of legal systematic research conducted byexamining library materials or secondary data. The main purpose is to identifythe main meanings or legal basisThe results of the research, there are two main things that can beconcluded, firstly that there is no regulation in positive law in Indonesia thatexplains how to implement the protection and application of the elderly who arein conflict with the law, so that policies that favor the protection of the elderlywho are in conflict with the law are needed, secondly Restorative justice takes therole of a mediator who is able to provide an agreement between the two parties.The perpetrators of criminal acts, in this case the elderly, have the opportunity toget legal remedies which do not require the perpetrators to get imprisonment butcan be replaced with criminal compensation or fines.Keywords: Elderly – Policy – Restorative Justice